Differential evolution metaheuristics for distributed limited-buffer flowshop scheduling with makespan criterion. (August 2019) - Zhang, Guanghui; Xing, Keyi
Highlights: We first address the distributed limited-buffer flowshop scheduling problem. We propose a continuous DE to efficiently solve the problem. We propose a discrete DE based on distributed properties for the problem. We validate the effective of different strategies in metaheuristics. We compare the proposals with efficient algorithms in the literature. Abstract: This paper addresses the distributed limited-buffer flowshop scheduling problem with makespan minimization criterion for the first time. The manufacturing layout consists of multiple homogeneous factories and each one is set as a permutation flowshop with limited buffers between any two adjacent machines. Compared with traditional single shop scheduling, this problem is more realistic because of the distribution and limited buffer constraints. Given that the NP-hardness, this paper focuses on the approximate approaches, and successively proposes two constructive heuristics for generating fast schedule and providing good initialization of meta-heuristics, a differential evolution algorithm run in continuous search space to further better the so-obtained schedules, and a discrete differential evolution algorithm implemented directly in combinatorial search space. Extensive experimental results validate that the performance of discrete differential evolution perform the best and other algorithms proposed in this paper are all with satisfactory evaluations.